2018
DOI: 10.1515/ap-2018-0021
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and serological investigation of infectious diseases in captive and free-range crab-eating fox (Cerdocyon thous – Linnaeus, 1776) from northeastern Brazil

Abstract: The aim of this study was to detect DNA and antibodies anti-Leishmania spp., Neospora caninum and Toxoplasma gondii in captive and free-range crab-eating fox (Cerdocyon thous) from northeastern Brazil. Twenty-five crab-eating foxes from different states of northeastern Brazil were sampled by this study. Blood samples were collected by cephalic or jugular vein punctures. The whole blood was submitted to PCR, and the sera samples to the serological analysis as follows: MAT for T. gondii, NAT for N. caninum, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 41 publications
1
4
0
1
Order By: Relevance
“…Molecular diagnosis by PCR identified L. infantum DNA in the animals assessed in our study and therefore confirms the occurrence of VL in foxes (Gontijo and Melo 2004). Likewise, some studies have already demonstrated the existence of a wild VL cycle, and the species C. thous as a potential reservoir for the parasite (Kruse et al 2004;Gomes et al 2007;Luppi et al 2008;Oliveira et al 2012;Ferreira et al 2013;Almeida et al 2018). Several factors can be associated with the occurrence of Leishmania among foxes.…”
Section: Resultssupporting
confidence: 83%
See 2 more Smart Citations
“…Molecular diagnosis by PCR identified L. infantum DNA in the animals assessed in our study and therefore confirms the occurrence of VL in foxes (Gontijo and Melo 2004). Likewise, some studies have already demonstrated the existence of a wild VL cycle, and the species C. thous as a potential reservoir for the parasite (Kruse et al 2004;Gomes et al 2007;Luppi et al 2008;Oliveira et al 2012;Ferreira et al 2013;Almeida et al 2018). Several factors can be associated with the occurrence of Leishmania among foxes.…”
Section: Resultssupporting
confidence: 83%
“…Currently, it is estimated about 30,000 new cases of VL and more than 1 million new cases of CL annually (WHO 2020). Remarkable, domestic dogs are important hosts of Leishmania species and can maintain the disease transmission cycle (Almeida et al 2018). Despite several studies investigating the occurrence and clinical manifestations of leishmaniasis in dogs, there few studies that describe the clinical evolution of the disease in other canids in Brazil (Oliveira 2012;Nicolato et al 2013).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found to be infected with L. infantum or exposed to the parasite (positive serology) in several publications, some of which were clinical cases, and thus were not considered in this study. The percentage of infection varied widely among the studies when including more than one animal (4-75%), and exposure to the parasite was demonstrated by serology (i.e., ELISA, IFAT), while culture, microscopy of smears, PCR followed by sequencing and inoculation of hamsters were employed to detect the parasite [81][82][83][84][85][86][87][88][89]. Several organs and tissues tested positive via PCR: bone marrow, heart, lymph nodes, liver, lungs, skin and spleen.…”
Section: Infantum In the Americasmentioning
confidence: 99%
“…These animals are a significant risk factor predisposing humans to infection in the endemic regions. However, other candidates include foxes and jackals (Millan et al 2016;Shokri et al 2017;Almeida et al 2018).…”
Section: Visceral Leishmaniasis (Vl)mentioning
confidence: 99%